An education in complexity: The role of contemporary art music - Pozzi, Raffaele (Musica Docta, 2013)
This paper provides some thoughts on the role of contemporary art music in the pedagogy of complexity. Today, theories of complexity are an area of thought that is largely established in the humanities and social sciences. They emphasize the importance of notions such as discontinuity, contradiction, non-linearity, multiplicity, randomness, and chaos in natural and cultural phenomena. The French epistemologist Edgar Morin, in a series of recent publications, has developed a pedagogy based on the theory of complexity. Contemporary art music contains a large repertoire of works, on which to build a pedagogy and didactics of complexity in music. The paper gives an example of use and didactic transposition of a piece, B.A.C.H. for solo piano (1970), by Italian composer Aldo Clementi.